Gender Differences in the Pathogenesis and Outcome of Lupus and of Lupus Nephritis - Schwartzman-Morris, Julie (Hindawi Publishing Corporation, 2012)
Systemic Lupus Erythematosus (SLE) typically affects females at far greater rates than males; however male SLE patients often have more severe disease than females. The gender disparities have been reported in clinical manifestations and in serological and hematological indices as well. In particular, SLE complicated with nephritis is more frequent in men than women, and several groups identified male gender as a risk factor for progression to renal failure. The specific differences in pathogenesis amongst genders have yet to be conclusively defined, though genetic, hormonal, and immune responses have been analyzed thus far. Further research is warranted to further elucidate these differences and permit the development of gender-tailored treatment regimens.